PENGARUH LITERASI PERPAJAKAN, MACHIAVELLIANISME DAN RASIONALITAS WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (STUDI KASUS WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KPP PRATAMA SERPONG) - Liani, Tara Pramudita; Barli, Harry (Publika Citra Media, 2024)
This study aims to analyze the influence of tax literacy, Machiavellianism, and taxpayer rationality on taxpayer compliance. This is a quantitative research with primary data sources. The population in this study is individual taxpayers registered at KPP Pratama Serpong. The sampling method used in this study is simple random sampling, applying the slovin formula, resulting in a final sample of 100 respondents. Data analysis techniques include multiple regression analysis with the assistance of Microsoft excel and SPSS version 20. The results of the study indicate the simultaneously, the variables of tax literacy, Machiavellianism, and taxpayer rationality affect taxpayer compliance. Partially, the results show that the variable of tax literacy affects taxpayer compliance. Meanwhile, the variable of Machiavellianism does not affect taxpayer compliance. And the variable of taxpayer rationality also does not affect taxpayer compliance.